The importance of microscopic examinations of eggshells: Discrimination of bioalteration and diagenetic overprints from biological features - Buscalioni, A.D.; Grellet-Tinner, G.; Corsetti, F. (Journal of Iberian Geology, 2010)
Although fossilization usually favors the preservation of calcium carbonate biominerals, diagenetic alterations might still produce erratic patterns that overprint the original biological structures. This investigation tries to discriminate in the fossil record “pathological” eggshells from diagenetic induced features as well as determine their origin, and aims, when possible, to provide alternative parsimonious interpretations to the origin of some of these rare and erratic features. In the past, most dinosaur eggshell studies failed to combine cathodoluminescence, scanning electron microscopy, transmitted and polarized light microscopic observations and were limited to only one or several of these examinations, which might have contributed to misinterpretations by lack of thorough observations. Sauropod eggshells from Faidella (Spain) and Auca Mahuevo (Argentina) provide ideal proxies to perform this research, as they display aberrant crystallographic features that have been or could be considered pathological. Under cathodoluminescence, the specimens fluoresce tremendously, indicating a strong diagenetic component in their make up. Guide by this information, further transmitted and polarized light microscopic examinations reveal microscopic dissolution fronts, which otherwise would have been left unnoted. The proposed hypothesis for the Faidella specimens in that organic filaments, which represent up to 2% of the shell composition, were exposed on the internal wall surfaces of pore canals where the calcium carbonate had been dissolved during a first diagenetic event. As such, the exposed extremities of the organic filaments likely triggered the formation of pseudo cores that mimic those in the membrana testacea during oogenesis. Observations based on the Argentinean specimens indicate that an added extra external structural layer is also separated from the original biological eggshell by a dissolution and recrystallization front. In addition to this abiotic process, artifact formations induced by bacterial mediation, a topic treated in an earlier publication, was also common at Auca Mahuevo. Without combined microscopic and cathodoluminiscence observations, the Faidella and Auca Mahuevo megaloolithid eggshells could be easily considered pathological eggshells. This would bias ensuing phylogenetic, paleobiological, and paleoenvironmental interpretations.